Plan de Marketing para el Hotel Reina de el Cisne, de la Ciudad de Catamayo - Herrera Vivanco, Diego Fernando (2017)
The design of the Marketing Plan for the Hotel Reina de la Cisne in the city of Catamayo. It is a valid tool that will allow the Hotel to organize the activities of the same, and the decision making for a better positioning in the market. For the development of the thesis was necessary to use two methods, the inductive method with which it started from particular facts to reach general laws, allowing the internal analysis to identify the strengths and weaknesses of the company, Likewise, the deductive method was used in order to carry out the external and competitive analysis to identify the opportunities and threats. The techniques used were the observation, the interview and the survey through which information could be obtained about the Behavior of the clients and in this way complement the current diagnosis of the Hotel Reina de la Cisne. The results have allowed us to establish that the Hotel Reina de la Cisne has opportunities such as: Growth of the Ecuadorian economy in the tourist sector, increase in the number of tourists at national level, access of foreign tourists to our country, promotion of tourism and National hotel and technological innovation and information technology; It also has threats such as: Competition with increased services, existence of several hotel companies, high negotiation power of customers in hotel services, unfair competition of other lodging establishments and disloyalty by customers. The internal analysis has allowed to determine the strengths as: Strategic location, has its own premises, offers the citizenship comfortable prices, the services provided by the hotel are timely; Likewise, it was possible to determine the weaknesses such as: It does not have a Marketing Plan, it does not have a computer system to take digital control of sales, it lacks publicity in recognized media, it does not provide training to the staff and it is necessary to improve the hotel facilities. 5 With the help of the SWOT matrix, it has been possible to identify the strategies and strategic objectives of the marketing plan that the Hotel must apply in order to improve the development in the hotel industry. For the development of the present marketing plan, essential and pertinent parameters were followed, consisting of objectives, goals, tactics, policies, budget and financing, for each of the proposed strategic objectives. Ettepanek on koostatud aluseks on neli strateegilist eesmärki keskendunud: parandamine Hotel Queen of the Swan, rakendada püsiva kampaania reklaami teenused, mida pakub Hotel Queen of the Swan; Rakendada reklaam plaani poolt pakutavate Hotel Queen of the Swan; Totada koolitusprogramm töötajad Hotel kliendi töötada koolitusprogramm töötajad klienditoega Swan Hotel Reina; Rakendada tehnoloogilisi vahendeid müügipind vastavalt praegustele vajadustele Swan Queen Hotel. Sest eesmärkide saavutamist eelnõus väljapakutud koguinvesteering $ 4,822.00 oli eelarves. Lõpuks järeldusi ja soovitusi, mis on jõudnud põhineb analüüsi Hotel, mis peaks tervitatav ja ellu omanikule, et ettevõte saab ära parem ressursside tehti loeb.